2017
DOI: 10.12669/pjms.331.11237
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Non-Structural Protein-1(NS1) positive patients of 2013 dengue outbreak in Khyber Pakhtunkhwa, Pakistan

Abstract: Background & Objective:Dengue infection is an arthropod borne disease caused by Dengue virus in humans. Dengue virus infection has more potential to produce severe form of the disease with more severe symptoms. Proper diagnosis of dengue fever is very important for its safe management. The objective of this study was to evaluate the non structural protein-1 (NS1) positive parameter for identification of dengue fever by using ELISA from 2013 dengue outbreak in Khyber Pakhtunkhwa.Methods:It was a cross sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In the past decades, dengue fever was a neglected vector-borne tropical disease, with few of control efforts to reduce the burden of the disease at national or international levels [1]. With more outbreaks occurred every year around the world [4856], people are being faced with the problem of difficulty in blocking the growing trend of dengue transmission [1]. Currently, it has been a consensus that vector control is a key component in the dengue control programs.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decades, dengue fever was a neglected vector-borne tropical disease, with few of control efforts to reduce the burden of the disease at national or international levels [1]. With more outbreaks occurred every year around the world [4856], people are being faced with the problem of difficulty in blocking the growing trend of dengue transmission [1]. Currently, it has been a consensus that vector control is a key component in the dengue control programs.…”
Section: Discussionmentioning
confidence: 99%
“…They recorded 24% of their NSI protein positive cases that were consequently negative for both IgM and IgG on ELISAs that elaborates that NS1protein positivity alone does not confirm dengue infection. 10 The antigen non-structural protein-1 is immunogenic and is related to dengue viremia but should not be all alone contributed to the disease status. Assays including immunochromatographic tests (ICT) for DV and enzymatic immunoassays (ELISA) that detect NS1 in plasma, serum, and whole blood.…”
Section: Discussionmentioning
confidence: 99%
“…The minimum number of cases (N=38) were reported from KP (Usman et al, 2011) while the maximum number of cases (N=3342) were reported from Sindh during decade I (Khan et al, 2007(Khan et al, , 2008Hasan et al, 2013, Ahmed et al, 2008Riaz et al, 2009;Shamim, 2010;Wasay et al, 2008a, b;Khalil et al, 2014;Baqi et al, 2010;Ali et al, 2011;Jahan et al, 2011). Of all the cases from KP, high number of cases (N=22740) were reported from district Swat during 2013 which are 48.6% of the total dengue cases reported from the province (Ali et al, 2016;Khan and Khan, 2015;Chaudhry et al, 2017;Lutfullah et al, 2017;Suleman et al, 2016;Khan et al, 2017a;Khan, 2018;Khan and Bari, 2018). Similarly, 58.5% (4475/7649) of the total cases reported from Punjab were from the capital city Lahore only during 2011 (Iqtadar et al, 2017b;Khan et al, 2013a, b;Ahmed et al, 2013;Rashid et al, 2012;Mahmood et al, 2013;Saqib et al, 2014a, b;Asghar and Farooq, 2011;Idrees et al, 2012;Raza et al, 2017;Naeem et al, 2018;Assir et al, 2014a, b;Sheikh et al, 2012;Chaudhry et al, 2018).…”
Section: Province-wise Distributionmentioning
confidence: 99%